2011
DOI: 10.5199/ijsmart-1791-874x-7b
|View full text |Cite
|
Sign up to set email alerts
|

Who Enters Campus Recreation Facilities: A Demographic Analysis

Abstract: The purpose of this study was to examine student entry into a campus recreation center based on seven demographics (gender, ethnicity, age, class standing, intercollegiate athlete vs. non-athlete, students with self-reported disability vs. non-disability, and campus residence) in order to determine who would be most likely to enter the recreation center. Subjects were from a mid-western, four year state-assisted institution with combined enrollment of 23,932 undergraduate and graduate students. Of the 23,932 e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 21 publications
0
21
0
Order By: Relevance
“…Lindsey and Sessoms (2006) found that female students were more likely to participate in campus recreational sports, while juniors and seniors consider these campus recreational programs as an important indicator of college selection. In contrast, some past research (Barcelona & Ross, 2002;Terzioğlu & Yazıcı, 2003;Young et al, 2003;Zizzi et al, 2004;Balcı & İlhan, 2006;Tekin et al, 2007;Miller et al, 2008;Lindsey et al, 2009;Lindsey, 2012;de Jager & Gbadamosi, 2013) found that male students were more likely to be participants and other earlier studies (Watson II et al, 2006;Miller et al, 2008;Milton & Patton, 2011) showed that lower-division students (freshmen and sophomores) were more likely to participate in campus recreational facilities. However, earlier research (Shank & Beasley, 1998;Frauman, 2005;Clemes et al, 2008;Sökmen, 2011;Moosmayer & Siems, 2012) indicated that there were no differences in the perceived importance of quality of campus life facilities with respect to students' gender.…”
Section: Review Of Related Literaturementioning
confidence: 88%
See 1 more Smart Citation
“…Lindsey and Sessoms (2006) found that female students were more likely to participate in campus recreational sports, while juniors and seniors consider these campus recreational programs as an important indicator of college selection. In contrast, some past research (Barcelona & Ross, 2002;Terzioğlu & Yazıcı, 2003;Young et al, 2003;Zizzi et al, 2004;Balcı & İlhan, 2006;Tekin et al, 2007;Miller et al, 2008;Lindsey et al, 2009;Lindsey, 2012;de Jager & Gbadamosi, 2013) found that male students were more likely to be participants and other earlier studies (Watson II et al, 2006;Miller et al, 2008;Milton & Patton, 2011) showed that lower-division students (freshmen and sophomores) were more likely to participate in campus recreational facilities. However, earlier research (Shank & Beasley, 1998;Frauman, 2005;Clemes et al, 2008;Sökmen, 2011;Moosmayer & Siems, 2012) indicated that there were no differences in the perceived importance of quality of campus life facilities with respect to students' gender.…”
Section: Review Of Related Literaturementioning
confidence: 88%
“…Marital status was also a contributing indicator, while results of a number of studies (Terzioğlu & Yazıcı, 2003;Frauman, 2005;Miller et al, 2008) revealed that married students were less likely to participate in campus recreational programs. Several studies mentioned that off-campus (Barcelona & Ross, 2002;Frauman, 2005) or on-campus students (Watson II et al, 2006;Miller et al, 2008;Milton & Patton, 2011) and part-time employed students (Frauman, 2005) were more likely to participate in campus recreational sports programs. Nevertheless, some earlier studies (Aldemir & Gülcan, 2003;Thomas & Galambos, 2004) found that demographic factors did not have an effect on students' satisfaction with campus facilities.…”
Section: Review Of Related Literaturementioning
confidence: 99%
“…This institution has observed 63% of the student population participating in this program. Participation is measured as unique users (Milton & Patton, 2011) who have entered the recreation facility at least once or registered for intramurals or club sports.…”
Section: Institutional Impact: Schoolmentioning
confidence: 99%
“…It is noteworthy that a majority of the club teams use the SRC for competition or practice. Participation is measured as unique users (Milton & Patton, 2011) who have entered the recreation facility at least once, registered for an intramural or club sport team, or who participated in a Campus Recreation organized event.…”
Section: Institutional Impact: Schoolmentioning
confidence: 99%
“…Findings in the age demographic indicated that fitness and wellness programs had significant effects on the knowledge base of participants regardless of age and that these programs indeed had a positive influence on student learning. The age differentiation, traditionally aged students vs. non-traditionally aged students is a frequently studied demographic in campus recreation participation research, most of it reporting that traditionally aged students were more likely to enter recreational facilities (Milton & Patton, 2011), were more likely to participate in organized campus recreational sports (Barcelona & Ross, 2002), and more likely to participate in campus recreation in general (Frauman, 2005) than were their nontraditionally aged counterparts. The results of this study do not contradict the aforementioned disparity in actual participation numbers between the two age groups; rather it validates the existence of such programs for both groups.…”
Section: Agementioning
confidence: 99%